Efficacy and safety of telavancin in clinical trials: a systematic review and meta-analysis. - Konstantinos A Polyzos; Michael N Mavros; Konstantinos Z Vardakas; Marinos C Makris; Petros I Rafailidis; Matthew E Falagas (PLoS ONE)
Introduction The epidemiology and antibiotic resistance of Staphylococcus aureus have evolved, underscoring the need for novel antibiotics, particularly against methicillin-resistant S. aureus (MRSA). Telavancin is a bactericidal lipoglycopeptide with potent activity against Gram-positive pathogens. Objective To systematically review and synthesize the available evidence from randomized controlled trials (RCTs) evaluating telavancin in the treatment of patients with infections due to Gram-positive organisms with the methodology of meta-analysis. Results Six RCTs comparing telavancin with vancomycin were included; 4 (2229 patients) referred to complicated skin and soft tissue infections (cSSTIs) and 2 (1503 patients) to hospital-acquired pneumonia (HAP). Regarding cSSTIs, telavancin and vancomycin showed comparable efficacy in clinically evaluable patients (odds ratio [OR] =1.10 [95% confidence intervals: 0.82-1.48]). Among patients with MRSA infection, telavancin showed higher eradication rates (OR=1.71 [1.08-2.70]) and a trend towards better clinical response (OR=1.55 [0.93-2.58]). Regarding HAP, telavancin was non-inferior to vancomycin in terms of clinical response in two Phase III RCTs; mortality rates for the pooled trials were comparable with telavancin (20%) and vancomycin (18.6%). Pooled data from cSSTIs and HAP studies on telavancin 10 mg/kg indicated higher rates of serum creatinine increases (OR=2.22 [1.38-3.57]), serious adverse events (OR=1.53 [1.05-2.24]), and adverse event-related withdrawals (OR=1.49 [1.14-1.95]) among telavancin recipients. Conclusion Telavancin might be an alternative to vancomycin in cases of difficult-to-treat MRSA infections. The potent antistaphylococcal activity of telavancin should be weighted against the potential for nephrotoxicity.